O efeito de diferentes durações de luz sobre a aquisição e manutenção da resposta de pressão à barra com atraso de reforço - Panetta, Paulo André Barbosa (2007)
Fifteen rats were randomized to one of the five following groups (with three rats in each group) to examine the effects of different durations of light ( delay signal ) upon the response acquisition and maintenance of lever press with delayed reinforcement, on the absence of shaping. Two phases construct the experiment, with fifteen experimental sessions and two sessions in extinction on each phase. For the rats randomized to Chain II Group, when Phase 1 was initiated, the duration of the light was initially the same of the delay, but was reduced gradually across phase until it was no longer present with the delay period. For rats randomized to Chain III Group, there was no delay signal initially, but its duration was increased across phase until it equalized the duration of the programmed delay (4 s). The duration of the delay signal was always the same of the delay for the rats employed on Chain I Group, while the was no delay signal for rats randomized to Tand Group. With the rats randomized to the Control Group there was no delay on reinforcement. Within subjects, response rates where higher as the duration of the delay signal increased, with the highest acceleration when its duration was minimal. Response rates where higher also to prior rates when the duration of the delay signal was reduced, with the highest acceleration when its duration was minimal. The findings are discussed in terms of the conditioned reinforcement of the delay signal by reduction the delay between its onset and the reinforcer